Real-World Efficacy and Safety of Ruxolitinib in Steroid-Refractory Graft-Versus-Host Disease: A Multicenter Retrospective Study From Turkey - Bakirtas, Mehmet; Berber, Lhami; Hindilerden, Ipek Yonal; Dal, Mehmet Sinan; Guner, Sebnem Izmir; Uysal, Ayse; Altuntasmd, Fevzi (Cig Media Group, Lp, 2025)
[Abstract Not Available]
Keywords: CT; graft-versus-host disease (GVHD); ruxolitinib; steroid-refractory GVHD; allogeneic hematopoietic stem cell transplantation (allo-HSCT); real-world evidence